PERENCANAAN DESAIN DRAINASE BERBASIS DATA PENGINDERAAN JAUH PADA TAMBANG TERBUKA PT. SDIC PAPUA CEMENT KABUPATEN MANOKWARI - Aldi Fariz Valderama; Sudaryatno; Taufik Hery Purwanto (INTAN Jurnal Penelitian Tambang, 2021)
Mining is an activity that is done to take materials that have economic value, mining activities are activities that change the land and change the shape of the topography. This change in shape can have a significant impact on surface runoff (Run Off) changes. The calculation of runoff coefficients uses The Hassing Method by utilizing remote sensing data and using rational methods to calculate surface runoff discharge. The purpose of this research is to know the good drainage design at mining sites PT. SDIC Papua Cement by using remote sensing data and Geographic Information System (SIG). The remote sensing data used is PlanetScope imagery and DEM data from AlosPalsar imagery. The accuracy test result obtained by PlanetScope imagery has an accuracy rate of 90.9%. Based on the data of the highest rainfall at the location of 189.6 mm. The result of runoff coefficient using The Hassing Method in the rain catchment area 1 (DTH 1) obtained a result of 0.51. With the discharge of surface runoff using Rational Method obtained the result of 0.3 m³/second. The result of the calculation of drainage design with the basic width of drainage (b) of 0.39 meters, the surface height of the channel base (y) of 0.47 meters, total drainage height (Tt) of 0.88 meters, the width of water surface (Ta) obtained results of 1.35 meters and width of drainage channels (Ts) is 1.72 meters.